Spacing strategies for enhancing drought resilience and yield in maize agriculture - Frantová Nicole; Porčová Lenka; Jovanović Ivana; Elzner Petr; Cerkal Radim; Rábek Michal (Open Agriculture, 2024)
This study investigates the impact of row spacing management on the yield, tillering, and water retention capacities of two maize varieties (F1 hybrids): Alombo (FAO 240) and SY Ignis (FAO 320). Through a comprehensive field experiment, we explored how varying inter-row and intra-row spacings influence plant physiological traits, including tillering frequency, relative water content (RWC), and yield components such as ear weight, seed number, and thousand kernel weight. Our findings demonstrate that narrower inter-row spacing (0.375 m) coupled with wider intra-row spacing (0.33 m) compared to inter-row spacing (0.75 m) with intra-row spacing (0.16 m) significantly enhances tillering, RWC, and grain yield, particularly for SY Ignis. The study reveals that tillering variability, influenced by spatial arrangement, serves as a potential indicator of yield outcomes, with increased tillering associated with higher biomass production and grain yield. Additionally, the research highlights the critical role of precise spatial arrangement in optimizing maize hydration, underscoring the strategic balance between inter-row and intra-row spacing for maintaining optimal moisture levels and supporting plant health. The results underscore the complexity of row spacing effects, which are not only variety-specific but also dependent on environmental and site-specific conditions, advocating for the adoption of tailored agricultural management practices to optimize crop production efficiency, especially under changing climate conditions.